Distribusi Diameter Jati dan Mahoni di Hutan Rakyat Desa Semoyo Kecamatan Patuk Kabupaten Gunungkidul - Suhartati, Tatik; Purwadi; Saputra, Evan (Fakultas Kehutanan Institut Pertanian STIPER Yogyakarta, 2022)
Community forests in Gunungkidul have developed for a long time and are managed in a traditional way, known as pekarangan, moor and wono. Most of the community forest planting patterns found in Semoyo Village are agroforestry patterns, where trees are planted with a mix of various tree species and one type is dominated, for example teak or mahogany. This study aims to determine the differences in the shape of the diameter distribution of mahogany and teak in dry fields and yards which are dominated by one tree species. The method used is quantitative analysis to produce diameter distribution and draw a curve to describe the stand structure. The results showed that for the type of mahogany in the yard and moor in all class diameters, the number of trees was higher than teak. The diameter distribution of mahogany and teak both in the yard and dry land both showed a shape that resembled an inverted J and was successfully modeled using the exponential model.